2015
DOI: 10.1007/s00125-015-3718-1
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic triacylglycerol distribution in type 2 diabetes

Abstract: colleagues concluded that there was no fat in the parenchymal tissue of the pancreas, and hence local release of fatty acids could not influence endocrine function [1]. The authors describe intralobular fat within the pancreas as detected by spectroscopy but then concluded that there was no fat in the parenchyma of the pancreas. This conclusion relied upon magnetic resonance (MR) techniques. We draw attention to three serious errors in the MR methodology employed, and to the sound evidence for the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
13
1
Order By: Relevance
“…The second issue raised by Hollingsworth et al is that we reported no fat within pancreatic parenchymal tissue, which contradicts their findings of a 3.3-6.2% fat fraction in the pancreas of type 2 diabetic humans [1]. In our paper, we stated that the MRI measurements revealed regions of parenchymal tissue void of any relevant lipid accumulation in all participants, which can be taken as evidence against a uniform pancreatic steatosis.…”
Section: Abbreviations Mdixon Modified Dixon Fat/water Imaging Sequencontrasting
confidence: 81%
See 3 more Smart Citations
“…The second issue raised by Hollingsworth et al is that we reported no fat within pancreatic parenchymal tissue, which contradicts their findings of a 3.3-6.2% fat fraction in the pancreas of type 2 diabetic humans [1]. In our paper, we stated that the MRI measurements revealed regions of parenchymal tissue void of any relevant lipid accumulation in all participants, which can be taken as evidence against a uniform pancreatic steatosis.…”
Section: Abbreviations Mdixon Modified Dixon Fat/water Imaging Sequencontrasting
confidence: 81%
“…Thus, it is misleading for Hollingsworth et al to claim that we suggest that there is no fat within the pancreatic parenchymal tissue. The lower pancreas fat fraction reported by us [2] compared Hollingsworth et al [1] is probably due to the noise bias, which does not seem to be corrected for in their method [4].…”
Section: Abbreviations Mdixon Modified Dixon Fat/water Imaging Sequenmentioning
confidence: 68%
See 2 more Smart Citations
“…The role of pancreatic steatosis in the pathogenesis of type 2 diabetes is currently under discussion and may depend on additional risk factors [1][2][3]. Fat accumulation in the pancreas is associated with reduced insulin secretion in glucose intolerant humans [4].…”
Section: Introductionmentioning
confidence: 99%